IDENTIFIKASI KOMPETENSI TENAGA AHLI PELAKSANA KONSTRUKSI PERUMAHAN DI YOGYAKARTA - Musyafa, Albani (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2015)
Indonesian society is currently experiencing a huge backlog in livable house. The backlog tends to grow in line with the conditions of insufficient supply and growing demand. In accordance with the government's program increasing the production of livable housing, human resources in the field of housing industry should be prepared well. One of the important human resources is the expert in the execution of housing constructions. The experts should have competences needed so that the construction can be executed efficiently and effectively. The objective of this study was to determine the sequence of critical competencies that should be mastered by the expert in execution of housing construction. This result is useful for improving the quality of education and training of human resources in the field of housing construction to overcome the backlog of livable house in Indonesia. The research method involves two main steps: the data collection and data processing methods. The competences and the important level were collected from the housing developers through interviews and questionnaires. The interview is intended to determine the types of competencies while questionnaire intended to determine the level of importance. The importance was validated with Kendal-W (Kendall's Coefficient of Concordance). The result shows two groups of competencies that should be mastered by the experts in execution of housing construction: 1. pre-construction phase, and 2. construction phase. In the pre-construction phase, the expert should master in: shop drawing, site plan for construction, budgeting/scheduling, workforce planning, mapping, health and safety issues, and the contract. While at the construction phase, the expert should master in methods of: scaffolding/formwork, reinforcement, roof framing, concreting, time/quality control, electrical/plumbing work, and material/equipment management.